Peran Loyalitas Sebagai Mediasi Team Work Dan Team Communication Terhadap Kinerja Karyawan Pada PT. Victory International Futures Semarang - Zeni Alya Salsabella; Rr. Hawik Ervina Indiworo; Ratih Hesty Utami P (Manivest : Jurnal Manajemen, Ekonomi, Kewirausahaan, dan Investasi, 2023)
This study departs from findings which show that communication in the company does not appear to be going well, this can be seen from the lack of employees being invited to discuss, and the absence of a forum to convey employee complaints, lack of contribution from each other and maximum work commitment. Apart from that, there is a Research Gap between Team Work on Employee Performance, and Team Communication on Employee Performance, and the phenomenon of Employee Labor Turnover Levels at PT. Victory International Futures Semarang which is based on company data.Departing from these problems, this research was prepared based on the role of loyalty as a mediator of team work and team communication on employee performance. This research is quantitative research with data collection techniques using questionnaires. The population used in this research were all employees, namely 105 employees at PT Victory International Futures Semarang. Testing was carried out using SmartPLS 3.0 (Partial Least Square) measurements.The test results show that the team work variable has a positive effect on loyalty with a P-Value value of (0.019), the team communication variable has a positive effect on loyalty with a P-Value value of (0.000), the loyalty variable has a positive effect on employee performance with a P-Value value amounting to (0.006), the team work variable has a positive effect on employee performance with a P-Value value of (0.000), the team communication variable has less influence on employee performance with a P-Value value of (0.135), the team work variable has no effect on employee performance through loyalty with a P-Value value of (0.144), while the team communication variable influences employee performance through loyalty with a P-Value value of (0.007). Keywords: Team Work, Team Communication, Loyalty, and Employee Performance.